Pengenalan Ekosistem Terumbu Karang Terhadap Amgpm Cabang Elim 1 – Amahusu Ambon - Aneila Stephanie Russel; Josepina Inggriany Untailawan; Nur Andini; Lukman Hamsah Djari; Ronald Darlly Hukubun (Yayasan Literasi Sains Indonesia, 2022)
The coral reef ecosystem in Amahusu village has been damaged, resulting in reduced production of fisheries and other animal products. This damage is continuously caused by natural and unnatural factors, so that it can disrupt the economy of fishing communities who depend on marine products for their daily lives. The purpose of this activity is to equip the Maluku Protestant Church Youth Troops (AMGPM) Nusaniwe sub- district, the basics of coral conservation through coral reef restoration activities. Coral transplantation is a method of restoring the condition of coral reefs to restore and restore the natural ecosystem of coral reefs. The methods include: introduction of coral transplantation, preparation and process of coral transplantation. The introduction of coral biota is the most basic thing that the public must know in order to understand the potential and role of corals in the coral reef ecosystem. In addition, the community is gradually being taught how to use the correct transplant method, hopefully in the future they will be independent and able to do it themselves. Coral transplantation is one method of coral reef restoration in Amahusu Village. This presentation is a deep understanding of the community that with significant assistance they are expected to be independent in protecting coral reefs.